Identifying the risk of suicide among adolescents admitted to a children's hospital using the Ask Suicide‐Screening Questions. Issue 2 (25th April 2019) - Inman, Dianna D.; Matthews, Joanne; Butcher, Lisa; Swartz, Colleen; Meadows, Amy Lynn
Abstract: Problem: Suicides are now the second leading cause of death among teenagers and young adults, 10–24. Many people who die by suicide visit a healthcare provider in the months before their death. Unfortunately, many healthcare clinicians do not routinely screen for mental health concerns such as suicide risk even though the American Academy of Pediatrics recommends screening adolescents for suicide risk. Methods: The Ask Suicide‐Screening Questions (aSQ), a four‐question screening instrument, was administered by nurses to all patients, 12 years and older, admitted to the general pediatric wards of a tertiary Children's Hospital. Nursing feedback and comfort levels were assessed before and after the 6‐week pilot program. Findings: During the 6 weeks, 152 eligible children were admitted to the general pediatric wards and 67 were screened using the ASQ; 3/67 had a nonacute "positive" screen and received a further psychiatric assessment. Conclusions: This pilot quality improvement initiative showed that suicide screening is feasible and acceptable to patients and families in a general pediatric inpatient setting. However, nurses would benefit from further teaching and training around asking suicide screening questions.